Studying the Level of Angiotensin II in Various Areas of Jordan with Different Altitudes - Haddad, Reema Kamal; Sweis, Jehan Fayez; Haddadin, Dafer; Aldalabih, Ramzi Abdallah; Aladaileh, Raya Mohammed; Abeeleh, Jaafar Abu; Abeeleh, Mahmoud Abu; Al-Shehabat, Mustafa Ahmad; Alkhatib, Ahed J (European Scientific Journal, ESJ, 2017)
Background and objectives: angiotensin II is involved in the development of hypertension. The main objectives of the study were to measure and compare the levels of angiotensin II among normal population in various areas with different altitudes Methods: Study design: cross- sectional study was conducted to collect data from participants at the same time. Study setting: participants from various areas with different altitudes were recruited to participate in this study. A total of 1500 participants were included. Study procedure: data was collected from participants based on a questionnaire that was constructed for this study. Blood samples were withdrawn from participants by a well- trained nurse. Angiotensin II was measured using enzyme linked immune sorbent assay (ELISA). Statistical analysis: data was analyzed using SPSS version 20. Data was represented as means, standard deviations, frequencies and percentage. The relationship between variables was tested using independent T-Test. The significance was considered at p value <0.05. Results: the level of angiotensin II was 8.84± 4.65 pg/ml in Dead Sea, 11.21± 6.05 pg/ml in Sea level, and 12.08± 5.19 pg/ml in Ajloun. There was a significant difference between the means of angiotensin II between Ajloun and Dead Sea (p=0.039). no other significant differences were observed between the study areas. Conclusion: the angiotensin II varies between the areas according to their altitudes and this consideration should be taken into account when hypertensive drugs are prescribed.